41.8k views
2 votes
For the curve defined implicitly by x^3 + y^2−2xy=2, find the slope of the tangent line at (-1,1). Write your answer either as an integer or a reduced fraction.

User Speldosa
by
5.2k points

2 Answers

2 votes

Answer:

-5/2

Explanation:

User Abdulwehab
by
4.7k points
5 votes

Answer:

Explanation:

The method you use is sort of a chain rule when you hit a y. Here's what I get

d(x^3)/dx = 3x^2

d(y^2)/dx = 2y * (dy/dx) This is where the chain rule comes in.

-d(2xy)/dy = -2y - 2x dy/dx

d(2)/dx = 0 Two is a constant. Its derivative = 0.

Now add these together.

3x^2 + 2y*(dy/dx) - 2y - 2x*(dy/dx) = 0

Now group the terms not containing dy/dx

3x^2 - 2y

And then group those containing dy/dx

2y (dy/dx) - 2x (dy/dx)

Pull out the common factor 2[dy/dx]

2 (dy/dx) [y - x]

Put the non dy/dx terms on the right

2(dy/dx) ( y + x) = - (3x^2 + 2y)

Divide both sides by 2(y - x)

(dy/dx) =
(-(3x^2+ 2y))/(2(-x + y))

You have the tangent expression. dy/dx is one expression for the tangent. The other is the fraction on the right.

You are almost home free.

Let x = - 1

Let y = 1

dy/dx = -(3(-1)^2 + 2(1) ) / (2(1 + 1)

dy/dx = -(3 + 2) /(2*2)

dy/dx = - (5)/4

dy/dx = - 1.25

Check my numbers pretty carefully. The method is correct. There are so many lines that the answer may not be.

User Tocs
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.